BACH1 mediates the antioxidant properties of aged garlic extract - Tsuneyoshi, Tadamitsu (Exp Ther Med, 2020)
In clinical studies, aged garlic extract (AGE) has been shown to improve endothelial dysfunction. The activation of nuclear factor erythroid 2 like 2 (Nrf2)-dependent gene expression is a proposed mechanism for maintaining vascular homeostasis. S−1-propenylcysteine (S1PC) and S-allylcysteine (SAC) are two predominant sulfur-containing amino acids present in AGE. However, it remains unclear as to whether the two sulfur amino acids activate Nrf2 in cells. Nitric oxide (NO) is an important signaling molecule and one of the activators of the Nrf2 pathway. In a previous study, we examined the effects of the two sulfur amino acids on NO signaling for modulating the Nrf2-dependent antioxidant response. Neither S1PC nor SAC were found to affect the expression of Nrf2-regulated genes, such as heme oxygenase-1 (HMOX1) in human umbilical vein endothelial cells. However, S1PC was found to augment HMOX1 expression, induced by NO donors, such as NOR3. NOR3 was found to induce the nuclear accumulation of NRF2 protein and concomitantly enhance the degradation of BTB domain and CNC homolog 1 (BACH1), a transcriptional repressor that competes with NRF2. Notably, on our previous study, S1PC enhanced the NOR3-induced downregulation of BACH1, but did not further enhance the NOR3-induced accumulation of NRF2. The findings of that study indicated that the S1PC-induced degradation of BACH1 may provide a basis for the antioxidant effects of AGE. Thus, in this review, we aimed to provide a current overview of the antioxidant effects of AGE and sulfur-containing amino acids.